Environmental regulation in the energy sector reform process of Latin America and the Caribbean. In: Energy magazine, v. 23, no. 4, p. 22-28. (2011)
Adds to the debate on environmental protection policy in the energy sector re-regulation process of Latin America and the Caribbean. Includes the results of the OLADE-ECLAC-G12 Project on Energy and Sustainable Development in LAM and the Caribbean.
Keywords: ENERGY POLICY; ENERGY SUPPLY; ENVIRONMENTAL PROTECTION; LATIN AMERICA; CARIBBEAN